(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article explores the concept of military psychology, focusing on the importance of strengthening mental resilience among soldiers. Mental resilience plays a crucial role in the military, where soldiers are constantly exposed to high-stress environments, combat situations, and demanding physical and psychological challenges. The ability to maintain psychological stability and cope with these challenges effectively is essential for ensuring both individual performance and overall mission success. This paper discusses the factors influencing mental resilience, the methods used to develop it, and the impact it has on soldiers’ well-being and operationAal effectiveness.